# Theory Infinite_Product_Measure

theory Infinite_Product_Measure
imports Projective_Family
```(*  Title:      HOL/Probability/Infinite_Product_Measure.thy
Author:     Johannes Hölzl, TU München
*)

section ‹Infinite Product Measure›

theory Infinite_Product_Measure
imports Probability_Measure Projective_Family
begin

lemma (in product_prob_space) distr_PiM_restrict_finite:
assumes "finite J" "J ⊆ I"
shows "distr (PiM I M) (PiM J M) (λx. restrict x J) = PiM J M"
proof (rule PiM_eqI)
fix X assume X: "⋀i. i ∈ J ⟹ X i ∈ sets (M i)"
{ fix J X assume J: "J ≠ {} ∨ I = {}" "finite J" "J ⊆ I" and X: "⋀i. i ∈ J ⟹ X i ∈ sets (M i)"
have "emeasure (PiM I M) (emb I J (Pi⇩E J X)) = (∏i∈J. M i (X i))"
proof (subst emeasure_extend_measure_Pair[OF PiM_def, where μ'=lim], goal_cases)
case 1 then show ?case
by (simp add: M.emeasure_space_1 emeasure_PiM Pi_iff sets_PiM_I_finite emeasure_lim_emb)
next
case (2 J X)
then have "emb I J (Pi⇩E J X) ∈ sets (PiM I M)"
by (intro measurable_prod_emb sets_PiM_I_finite) auto
from this[THEN sets.sets_into_space] show ?case
qed (insert assms J X, simp_all del: sets_lim
note * = this

have "emeasure (PiM I M) (emb I J (Pi⇩E J X)) = (∏i∈J. M i (X i))"
proof (cases "J ≠ {} ∨ I = {}")
case False
then obtain i where i: "J = {}" "i ∈ I" by auto
then have "emb I {} {λx. undefined} = emb I {i} (Π⇩E i∈{i}. space (M i))"
by (auto simp: space_PiM prod_emb_def)
with i show ?thesis
next
case True
then show ?thesis
by (simp add: *[OF _ assms X])
qed
with assms show "emeasure (distr (Pi⇩M I M) (Pi⇩M J M) (λx. restrict x J)) (Pi⇩E J X) = (∏i∈J. emeasure (M i) (X i))"
by (subst emeasure_distr_restrict[OF _ refl]) (auto intro!: sets_PiM_I_finite X)
qed (insert assms, auto)

lemma (in product_prob_space) emeasure_PiM_emb':
"J ⊆ I ⟹ finite J ⟹ X ∈ sets (PiM J M) ⟹ emeasure (Pi⇩M I M) (emb I J X) = PiM J M X"
by (subst distr_PiM_restrict_finite[symmetric, of J])
(auto intro!: emeasure_distr_restrict[symmetric])

lemma (in product_prob_space) emeasure_PiM_emb:
"J ⊆ I ⟹ finite J ⟹ (⋀i. i ∈ J ⟹ X i ∈ sets (M i)) ⟹
emeasure (Pi⇩M I M) (emb I J (Pi⇩E J X)) = (∏ i∈J. emeasure (M i) (X i))"
by (subst emeasure_PiM_emb') (auto intro!: emeasure_PiM)

sublocale product_prob_space ⊆ P?: prob_space "Pi⇩M I M"
proof
have *: "emb I {} {λx. undefined} = space (PiM I M)"
by (auto simp: prod_emb_def space_PiM)
show "emeasure (Pi⇩M I M) (space (Pi⇩M I M)) = 1"
using emeasure_PiM_emb[of "{}" "λ_. {}"] by (simp add: *)
qed

lemma prob_space_PiM:
assumes M: "⋀i. i ∈ I ⟹ prob_space (M i)" shows "prob_space (PiM I M)"
proof -
let ?M = "λi. if i ∈ I then M i else count_space {undefined}"
interpret M': prob_space "?M i" for i
using M by (cases "i ∈ I") (auto intro!: prob_spaceI)
interpret product_prob_space ?M I
by unfold_locales
have "prob_space (Π⇩M i∈I. ?M i)"
by unfold_locales
also have "(Π⇩M i∈I. ?M i) = (Π⇩M i∈I. M i)"
by (intro PiM_cong) auto
finally show ?thesis .
qed

lemma (in product_prob_space) emeasure_PiM_Collect:
assumes X: "J ⊆ I" "finite J" "⋀i. i ∈ J ⟹ X i ∈ sets (M i)"
shows "emeasure (Pi⇩M I M) {x∈space (Pi⇩M I M). ∀i∈J. x i ∈ X i} = (∏ i∈J. emeasure (M i) (X i))"
proof -
have "{x∈space (Pi⇩M I M). ∀i∈J. x i ∈ X i} = emb I J (Pi⇩E J X)"
unfolding prod_emb_def using assms by (auto simp: space_PiM Pi_iff)
with emeasure_PiM_emb[OF assms] show ?thesis by simp
qed

lemma (in product_prob_space) emeasure_PiM_Collect_single:
assumes X: "i ∈ I" "A ∈ sets (M i)"
shows "emeasure (Pi⇩M I M) {x∈space (Pi⇩M I M). x i ∈ A} = emeasure (M i) A"
using emeasure_PiM_Collect[of "{i}" "λi. A"] assms
by simp

lemma (in product_prob_space) measure_PiM_emb:
assumes "J ⊆ I" "finite J" "⋀i. i ∈ J ⟹ X i ∈ sets (M i)"
shows "measure (PiM I M) (emb I J (Pi⇩E J X)) = (∏ i∈J. measure (M i) (X i))"
using emeasure_PiM_emb[OF assms]
unfolding emeasure_eq_measure M.emeasure_eq_measure
by (simp add: prod_ennreal measure_nonneg prod_nonneg)

lemma sets_Collect_single':
"i ∈ I ⟹ {x∈space (M i). P x} ∈ sets (M i) ⟹ {x∈space (PiM I M). P (x i)} ∈ sets (PiM I M)"
using sets_Collect_single[of i I "{x∈space (M i). P x}" M]
by (simp add: space_PiM PiE_iff cong: conj_cong)

lemma (in finite_product_prob_space) finite_measure_PiM_emb:
"(⋀i. i ∈ I ⟹ A i ∈ sets (M i)) ⟹ measure (PiM I M) (Pi⇩E I A) = (∏i∈I. measure (M i) (A i))"
using measure_PiM_emb[of I A] finite_index prod_emb_PiE_same_index[OF sets.sets_into_space, of I A M]
by auto

lemma (in product_prob_space) PiM_component:
assumes "i ∈ I"
shows "distr (PiM I M) (M i) (λω. ω i) = M i"
proof (rule measure_eqI[symmetric])
fix A assume "A ∈ sets (M i)"
moreover have "((λω. ω i) -` A ∩ space (PiM I M)) = {x∈space (PiM I M). x i ∈ A}"
by auto
ultimately show "emeasure (M i) A = emeasure (distr (PiM I M) (M i) (λω. ω i)) A"
by (auto simp: ‹i∈I› emeasure_distr measurable_component_singleton emeasure_PiM_Collect_single)
qed simp

lemma (in product_prob_space) PiM_eq:
assumes M': "sets M' = sets (PiM I M)"
assumes eq: "⋀J F. finite J ⟹ J ⊆ I ⟹ (⋀j. j ∈ J ⟹ F j ∈ sets (M j)) ⟹
emeasure M' (prod_emb I M J (Π⇩E j∈J. F j)) = (∏j∈J. emeasure (M j) (F j))"
shows "M' = (PiM I M)"
proof (rule measure_eqI_PiM_infinite[symmetric, OF refl M'])
show "finite_measure (Pi⇩M I M)"

lemma (in product_prob_space) AE_component: "i ∈ I ⟹ AE x in M i. P x ⟹ AE x in PiM I M. P (x i)"
apply (rule AE_distrD[of "λω. ω i" "PiM I M" "M i" P])
apply simp
apply (subst PiM_component)
apply simp_all
done

lemma emeasure_PiM_emb:
assumes M: "⋀i. i ∈ I ⟹ prob_space (M i)"
assumes J: "J ⊆ I" "finite J" and A: "⋀i. i ∈ J ⟹ A i ∈ sets (M i)"
shows "emeasure (Pi⇩M I M) (prod_emb I M J (Pi⇩E J A)) = (∏i∈J. emeasure (M i) (A i))"
proof -
let ?M = "λi. if i ∈ I then M i else count_space {undefined}"
interpret M': prob_space "?M i" for i
using M by (cases "i ∈ I") (auto intro!: prob_spaceI)
interpret P: product_prob_space ?M I
by unfold_locales
have "emeasure (Pi⇩M I M) (prod_emb I M J (Pi⇩E J A)) = emeasure (Pi⇩M I ?M) (P.emb I J (Pi⇩E J A))"
by (auto simp: prod_emb_def PiE_iff intro!: arg_cong2[where f=emeasure] PiM_cong)
also have "… = (∏i∈J. emeasure (M i) (A i))"
using J A by (subst P.emeasure_PiM_emb[OF J]) (auto intro!: prod.cong)
finally show ?thesis .
qed

lemma distr_pair_PiM_eq_PiM:
fixes i' :: "'i" and I :: "'i set" and M :: "'i ⇒ 'a measure"
assumes M: "⋀i. i ∈ I ⟹ prob_space (M i)" "prob_space (M i')"
shows "distr (M i' ⨂⇩M (Π⇩M i∈I. M i)) (Π⇩M i∈insert i' I. M i) (λ(x, X). X(i' := x)) =
(Π⇩M i∈insert i' I. M i)" (is "?L = _")
proof (rule measure_eqI_PiM_infinite[symmetric, OF refl])
interpret M': prob_space "M i'" by fact
interpret I: prob_space "(Π⇩M i∈I. M i)"
using M by (intro prob_space_PiM) auto
interpret I': prob_space "(Π⇩M i∈insert i' I. M i)"
using M by (intro prob_space_PiM) auto
show "finite_measure (Π⇩M i∈insert i' I. M i)"
by unfold_locales
fix J A assume J: "finite J" "J ⊆ insert i' I" and A: "⋀i. i ∈ J ⟹ A i ∈ sets (M i)"
let ?X = "prod_emb (insert i' I) M J (Pi⇩E J A)"
have "Pi⇩M (insert i' I) M ?X = (∏i∈J. M i (A i))"
using M J A by (intro emeasure_PiM_emb) auto
also have "… = M i' (if i' ∈ J then (A i') else space (M i')) * (∏i∈J-{i'}. M i (A i))"
using prod.insert_remove[of J "λi. M i (A i)" i'] J M'.emeasure_space_1
by (cases "i' ∈ J") (auto simp: insert_absorb)
also have "(∏i∈J-{i'}. M i (A i)) = Pi⇩M I M (prod_emb I M (J - {i'}) (Pi⇩E (J - {i'}) A))"
using M J A by (intro emeasure_PiM_emb[symmetric]) auto
also have "M i' (if i' ∈ J then (A i') else space (M i')) * … =
(M i' ⨂⇩M Pi⇩M I M) ((if i' ∈ J then (A i') else space (M i')) × prod_emb I M (J - {i'}) (Pi⇩E (J - {i'}) A))"
using J A by (intro I.emeasure_pair_measure_Times[symmetric] sets_PiM_I) auto
also have "((if i' ∈ J then (A i') else space (M i')) × prod_emb I M (J - {i'}) (Pi⇩E (J - {i'}) A)) =
(λ(x, X). X(i' := x)) -` ?X ∩ space (M i' ⨂⇩M Pi⇩M I M)"
using A[of i', THEN sets.sets_into_space] unfolding set_eq_iff
by (simp add: prod_emb_def space_pair_measure space_PiM PiE_fun_upd ac_simps cong: conj_cong)
(auto simp add: Pi_iff Ball_def all_conj_distrib)
finally show "Pi⇩M (insert i' I) M ?X = ?L ?X"
using J A by (simp add: emeasure_distr)
qed simp

lemma distr_PiM_reindex:
assumes M: "⋀i. i ∈ K ⟹ prob_space (M i)"
assumes f: "inj_on f I" "f ∈ I → K"
shows "distr (Pi⇩M K M) (Π⇩M i∈I. M (f i)) (λω. λn∈I. ω (f n)) = (Π⇩M i∈I. M (f i))"
(is "distr ?K ?I ?t = ?I")
proof (rule measure_eqI_PiM_infinite[symmetric, OF refl])
interpret prob_space ?I
using f M by (intro prob_space_PiM) auto
show "finite_measure ?I"
by unfold_locales
fix A J assume J: "finite J" "J ⊆ I" and A: "⋀i. i ∈ J ⟹ A i ∈ sets (M (f i))"
have [simp]: "i ∈ J ⟹ the_inv_into I f (f i) = i" for i
using J f by (intro the_inv_into_f_f) auto
have "?I (prod_emb I (λi. M (f i)) J (Pi⇩E J A)) = (∏j∈J. M (f j) (A j))"
using f J A by (intro emeasure_PiM_emb M) auto
also have "… = (∏j∈f`J. M j (A (the_inv_into I f j)))"
using f J by (subst prod.reindex) (auto intro!: prod.cong intro: inj_on_subset simp: the_inv_into_f_f)
also have "… = ?K (prod_emb K M (f`J) (Π⇩E j∈f`J. A (the_inv_into I f j)))"
using f J A by (intro emeasure_PiM_emb[symmetric] M) (auto simp: the_inv_into_f_f)
also have "prod_emb K M (f`J) (Π⇩E j∈f`J. A (the_inv_into I f j)) = ?t -` prod_emb I (λi. M (f i)) J (Pi⇩E J A) ∩ space ?K"
using f J A by (auto simp: prod_emb_def space_PiM Pi_iff PiE_iff Int_absorb1)
also have "?K … = distr ?K ?I ?t (prod_emb I (λi. M (f i)) J (Pi⇩E J A))"
using f J A by (intro emeasure_distr[symmetric] sets_PiM_I) (auto simp: Pi_iff)
finally show "?I (prod_emb I (λi. M (f i)) J (Pi⇩E J A)) = distr ?K ?I ?t (prod_emb I (λi. M (f i)) J (Pi⇩E J A))" .
qed simp

lemma distr_PiM_component:
assumes M: "⋀i. i ∈ I ⟹ prob_space (M i)"
assumes "i ∈ I"
shows "distr (Pi⇩M I M) (M i) (λω. ω i) = M i"
proof -
have *: "(λω. ω i) -` A ∩ space (Pi⇩M I M) = prod_emb I M {i} (Π⇩E i'∈{i}. A)" for A
by (auto simp: prod_emb_def space_PiM)
show ?thesis
apply (intro measure_eqI)
apply (auto simp add: emeasure_distr ‹i∈I› * emeasure_PiM_emb M)
apply (subst emeasure_PiM_emb)
done
qed

lemma AE_PiM_component:
"(⋀i. i ∈ I ⟹ prob_space (M i)) ⟹ i ∈ I ⟹ AE x in M i. P x ⟹ AE x in PiM I M. P (x i)"
using AE_distrD[of "λx. x i" "PiM I M" "M i"]
by (subst (asm) distr_PiM_component[of I _ i]) (auto intro: AE_distrD[of "λx. x i" _ _ P])

lemma decseq_emb_PiE:
"incseq J ⟹ decseq (λi. prod_emb I M (J i) (Π⇩E j∈J i. X j))"
by (fastforce simp: decseq_def prod_emb_def incseq_def Pi_iff)

subsection ‹Sequence space›

definition comb_seq :: "nat ⇒ (nat ⇒ 'a) ⇒ (nat ⇒ 'a) ⇒ (nat ⇒ 'a)" where
"comb_seq i ω ω' j = (if j < i then ω j else ω' (j - i))"

lemma split_comb_seq: "P (comb_seq i ω ω' j) ⟷ (j < i ⟶ P (ω j)) ∧ (∀k. j = i + k ⟶ P (ω' k))"
by (auto simp: comb_seq_def not_less)

lemma split_comb_seq_asm: "P (comb_seq i ω ω' j) ⟷ ¬ ((j < i ∧ ¬ P (ω j)) ∨ (∃k. j = i + k ∧ ¬ P (ω' k)))"
by (auto simp: comb_seq_def)

lemma measurable_comb_seq:
"(λ(ω, ω'). comb_seq i ω ω') ∈ measurable ((Π⇩M i∈UNIV. M) ⨂⇩M (Π⇩M i∈UNIV. M)) (Π⇩M i∈UNIV. M)"
proof (rule measurable_PiM_single)
show "(λ(ω, ω'). comb_seq i ω ω') ∈ space ((Π⇩M i∈UNIV. M) ⨂⇩M (Π⇩M i∈UNIV. M)) → (UNIV →⇩E space M)"
by (auto simp: space_pair_measure space_PiM PiE_iff split: split_comb_seq)
fix j :: nat and A assume A: "A ∈ sets M"
then have *: "{ω ∈ space ((Π⇩M i∈UNIV. M) ⨂⇩M (Π⇩M i∈UNIV. M)). case_prod (comb_seq i) ω j ∈ A} =
(if j < i then {ω ∈ space (Π⇩M i∈UNIV. M). ω j ∈ A} × space (Π⇩M i∈UNIV. M)
else space (Π⇩M i∈UNIV. M) × {ω ∈ space (Π⇩M i∈UNIV. M). ω (j - i) ∈ A})"
by (auto simp: space_PiM space_pair_measure comb_seq_def dest: sets.sets_into_space)
show "{ω ∈ space ((Π⇩M i∈UNIV. M) ⨂⇩M (Π⇩M i∈UNIV. M)). case_prod (comb_seq i) ω j ∈ A} ∈ sets ((Π⇩M i∈UNIV. M) ⨂⇩M (Π⇩M i∈UNIV. M))"
unfolding * by (auto simp: A intro!: sets_Collect_single)
qed

lemma measurable_comb_seq'[measurable (raw)]:
assumes f: "f ∈ measurable N (Π⇩M i∈UNIV. M)" and g: "g ∈ measurable N (Π⇩M i∈UNIV. M)"
shows "(λx. comb_seq i (f x) (g x)) ∈ measurable N (Π⇩M i∈UNIV. M)"
using measurable_compose[OF measurable_Pair[OF f g] measurable_comb_seq] by simp

lemma comb_seq_0: "comb_seq 0 ω ω' = ω'"

lemma comb_seq_Suc: "comb_seq (Suc n) ω ω' = comb_seq n ω (case_nat (ω n) ω')"
by (auto simp add: comb_seq_def not_less less_Suc_eq le_imp_diff_is_add intro!: ext split: nat.split)

lemma comb_seq_Suc_0[simp]: "comb_seq (Suc 0) ω = case_nat (ω 0)"
by (intro ext) (simp add: comb_seq_Suc comb_seq_0)

lemma comb_seq_less: "i < n ⟹ comb_seq n ω ω' i = ω i"
by (auto split: split_comb_seq)

lemma comb_seq_add: "comb_seq n ω ω' (i + n) = ω' i"
by (auto split: nat.split split_comb_seq)

lemma case_nat_comb_seq: "case_nat s' (comb_seq n ω ω') (i + n) = case_nat (case_nat s' ω n) ω' i"
by (auto split: nat.split split_comb_seq)

lemma case_nat_comb_seq':
"case_nat s (comb_seq i ω ω') = comb_seq (Suc i) (case_nat s ω) ω'"
by (auto split: split_comb_seq nat.split)

locale sequence_space = product_prob_space "λi. M" "UNIV :: nat set" for M
begin

abbreviation "S ≡ Π⇩M i∈UNIV::nat set. M"

lemma infprod_in_sets[intro]:
fixes E :: "nat ⇒ 'a set" assumes E: "⋀i. E i ∈ sets M"
shows "Pi UNIV E ∈ sets S"
proof -
have "Pi UNIV E = (⋂i. emb UNIV {..i} (Π⇩E j∈{..i}. E j))"
using E E[THEN sets.sets_into_space]
by (auto simp: prod_emb_def Pi_iff extensional_def)
with E show ?thesis by auto
qed

lemma measure_PiM_countable:
fixes E :: "nat ⇒ 'a set" assumes E: "⋀i. E i ∈ sets M"
shows "(λn. ∏i≤n. measure M (E i)) ⇢ measure S (Pi UNIV E)"
proof -
let ?E = "λn. emb UNIV {..n} (Pi⇩E {.. n} E)"
have "⋀n. (∏i≤n. measure M (E i)) = measure S (?E n)"
using E by (simp add: measure_PiM_emb)
moreover have "Pi UNIV E = (⋂n. ?E n)"
using E E[THEN sets.sets_into_space]
by (auto simp: prod_emb_def extensional_def Pi_iff)
moreover have "range ?E ⊆ sets S"
using E by auto
moreover have "decseq ?E"
by (auto simp: prod_emb_def Pi_iff decseq_def)
ultimately show ?thesis
qed

lemma nat_eq_diff_eq:
fixes a b c :: nat
shows "c ≤ b ⟹ a = b - c ⟷ a + c = b"
by auto

lemma PiM_comb_seq:
"distr (S ⨂⇩M S) S (λ(ω, ω'). comb_seq i ω ω') = S" (is "?D = _")
proof (rule PiM_eq)
let ?I = "UNIV::nat set" and ?M = "λn. M"
let "distr _ _ ?f" = "?D"

fix J E assume J: "finite J" "J ⊆ ?I" "⋀j. j ∈ J ⟹ E j ∈ sets M"
let ?X = "prod_emb ?I ?M J (Π⇩E j∈J. E j)"
have "⋀j x. j ∈ J ⟹ x ∈ E j ⟹ x ∈ space M"
using J(3)[THEN sets.sets_into_space] by (auto simp: space_PiM Pi_iff subset_eq)
with J have "?f -` ?X ∩ space (S ⨂⇩M S) =
(prod_emb ?I ?M (J ∩ {..<i}) (Π⇩E j∈J ∩ {..<i}. E j)) ×
(prod_emb ?I ?M ((op + i) -` J) (Π⇩E j∈(op + i) -` J. E (i + j)))" (is "_ = ?E × ?F")
by (auto simp: space_pair_measure space_PiM prod_emb_def all_conj_distrib PiE_iff
split: split_comb_seq split_comb_seq_asm)
then have "emeasure ?D ?X = emeasure (S ⨂⇩M S) (?E × ?F)"
by (subst emeasure_distr[OF measurable_comb_seq])
(auto intro!: sets_PiM_I simp: split_beta' J)
also have "… = emeasure S ?E * emeasure S ?F"
using J by (intro P.emeasure_pair_measure_Times)  (auto intro!: sets_PiM_I finite_vimageI simp: inj_on_def)
also have "emeasure S ?F = (∏j∈(op + i) -` J. emeasure M (E (i + j)))"
using J by (intro emeasure_PiM_emb) (simp_all add: finite_vimageI inj_on_def)
also have "… = (∏j∈J - (J ∩ {..<i}). emeasure M (E j))"
by (rule prod.reindex_cong [of "λx. x - i"])
(auto simp: image_iff Bex_def not_less nat_eq_diff_eq ac_simps cong: conj_cong intro!: inj_onI)
also have "emeasure S ?E = (∏j∈J ∩ {..<i}. emeasure M (E j))"
using J by (intro emeasure_PiM_emb) simp_all
also have "(∏j∈J ∩ {..<i}. emeasure M (E j)) * (∏j∈J - (J ∩ {..<i}). emeasure M (E j)) = (∏j∈J. emeasure M (E j))"
by (subst mult.commute) (auto simp: J prod.subset_diff[symmetric])
finally show "emeasure ?D ?X = (∏j∈J. emeasure M (E j))" .
qed simp_all

lemma PiM_iter:
"distr (M ⨂⇩M S) S (λ(s, ω). case_nat s ω) = S" (is "?D = _")
proof (rule PiM_eq)
let ?I = "UNIV::nat set" and ?M = "λn. M"
let "distr _ _ ?f" = "?D"

fix J E assume J: "finite J" "J ⊆ ?I" "⋀j. j ∈ J ⟹ E j ∈ sets M"
let ?X = "prod_emb ?I ?M J (Π⇩E j∈J. E j)"
have "⋀j x. j ∈ J ⟹ x ∈ E j ⟹ x ∈ space M"
using J(3)[THEN sets.sets_into_space] by (auto simp: space_PiM Pi_iff subset_eq)
with J have "?f -` ?X ∩ space (M ⨂⇩M S) = (if 0 ∈ J then E 0 else space M) ×
(prod_emb ?I ?M (Suc -` J) (Π⇩E j∈Suc -` J. E (Suc j)))" (is "_ = ?E × ?F")
by (auto simp: space_pair_measure space_PiM PiE_iff prod_emb_def all_conj_distrib
split: nat.split nat.split_asm)
then have "emeasure ?D ?X = emeasure (M ⨂⇩M S) (?E × ?F)"
by (subst emeasure_distr)
(auto intro!: sets_PiM_I simp: split_beta' J)
also have "… = emeasure M ?E * emeasure S ?F"
using J by (intro P.emeasure_pair_measure_Times) (auto intro!: sets_PiM_I finite_vimageI)
also have "emeasure S ?F = (∏j∈Suc -` J. emeasure M (E (Suc j)))"
using J by (intro emeasure_PiM_emb) (simp_all add: finite_vimageI)
also have "… = (∏j∈J - {0}. emeasure M (E j))"
by (rule prod.reindex_cong [of "λx. x - 1"])
(auto simp: image_iff Bex_def not_less nat_eq_diff_eq ac_simps cong: conj_cong intro!: inj_onI)
also have "emeasure M ?E * (∏j∈J - {0}. emeasure M (E j)) = (∏j∈J. emeasure M (E j))"
by (auto simp: M.emeasure_space_1 prod.remove J)
finally show "emeasure ?D ?X = (∏j∈J. emeasure M (E j))" .
qed simp_all

end

end
```